Modification of nitrile-terminated biphenylthiol self-assembled monolayers by electron irradiation and related applications - Meyerbröker, Nikolaus; Zharnikov, Michael (Langmuir, 2012)
Here we describe the behavior of self-assembled monolayers (SAMs) of 4′-cyanobiphenyl-4-thiol (CBPT) on Au(111) upon electron irradiation. Under such a treatment, the aromatic framework of CBPT SAMs is laterally cross-linked while the nitrile groups, located at the SAM-ambience interface, are reduced to active amine moieties which can be used as docking sites for the coupling of other species. This makes CBPT monolayers as a promising system for conventional and chemical lithography as well as for nanofabrication. Along these lines, we demonstrate the preparation of complex polymer brushes, patterning of the underlying substrate, and fabrication of molecule-thin, free-standing membranes on the basis of CBPT SAMs. The balance between the application-favorable processes and defragmentation in these films is studied in detail, and comparison to the well-established (for the relevant applications) system of 4′-nitrobiphenyl-4-thiols is performed. Taking CBPT SAMs as a model system, the effect of the energy of the primary electrons on the extent of the chemical transformation and cross-linking in substituted aromatic SAMs is investigated.